Effects of acute lymphoblastic leukemia on ceruloplasmin oxidase, copper and several markers of oxidative damage, in children - Mehdi, Wesen Adel; Yusof, Faridah; Mehde, Atheer Awad; Zainulabdeen, Jwan Abdulmohsin; Ahmad Raus, Raha; Abdulbari, Alaa Shawqi (UICC Asian Regional Office and the National Cancer Center of Korea, 2015)
Background: Acute leukaemia is characterized by fast growth of abnormal clones of haemopoietic precursor cells inside bone marrow leading to undue accumulation in the bone marrow. Acute lymphoblastic leukemia (ALL) is the most common form of childhood cancer. Materials and Methods: The study concerned 50 children diagnosed with ALL (mean age, 8.55±2.54) compared to 40 healthy controls (mean age, 8.00±1.85). The Hb, serum copper , ceruloplasmin oxidase, advanced oxidation protein products (AOPPs), total antioxidant activity (TAA) and protein were measured in all groups.One proteinous component was isolated by gel filtration chromatography from the precipitate produced by polyethylene glycol. Results: Significantly higher levels of AOPP, copper and decrease in total antioxidant activity were noted in the cases. Statistical analysis also showed a significant increase (p<0.01) in the activity of serum ceruloplasmin oxidase in patients with ALL compared to normal subjects .The maximum velocity (Vmax) and Michaelis constant had values of 104.2 U/L and 11.7 mM, respectively. The ΔH* values for ceruloplasmin oxidase in ALL patients were positive, confirming the reaction to be endothermic. Conclusions: The results from this study showed a significant increase in AOPP, ceruloplasmine oxidase and decrease in total antioxidant activity .These parameters may play a role in development of DNA damage in childhood patients with acute lymphoblastic leukemia (ALL).The ΔS* and ΔG* values were negative, these refer that the reaction of ES formation is spontaneous, but needs energy in a so-called endergonic reaction. Also the negative ΔS* value of ceruloplasmin oxidase indicates that the complex [ES*] is further modulated through increasing structure arrangement.